RESPON PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI PADI GOGO - Aliudin, Aliudin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
Conversion of agricultural land to non agricultural land can not be avoided, while the needs of rice continues to grow. To meet these needs , efforts to develop upland rice are needed. Upland rice can be grown on dry land, moor, or former forest land with minimal irrigation (rainfed). In general, farmers use the production factors uncontrolable, making it difficult to estimate the response of the use of production factors . Based on the research conducted in Cimarga Subdistrict Lebak District in 2010 plant season. This study aims to estimate the response of factors use on upland rice production. Thirty upland paddy farmers were selected using Simple Random Sampling dan Cobb – Douglas Model of upland paddy production was applied to analyse production factors response. The results showed: (a) a partial response acreage and volume of urea fertilizer on upland paddy farming is positive, while the number of labor and seed volume showed a negative effect (b) Simultaneously the four factors of production toward upland paddy production has a positive effect. Seed acreage and volume showed a positive response to the production of upland rice indicate that farmers still have a chance to increase acreage and seed use. On the contrary, the use of labor and fertilizer urea showed a negative response indicating that the use of these two production factors have already excessively, and farmers have to reduce the use of these production factors. Key words : production factors, farming, paddy of dry land